Addressing Organizational Cultural Conflicts in Engineering with Design Thinking. (30th July 2020) - Eddington, Sean M.; Corple, Danielle; Buzzanell, Patrice M.; Zoltowski, Carla; Brightman, Andrew
Abstract: The present study examined how design thinking processes help to facilitate difficult conversations for fostering organizational change toward greater inclusion and equity in undergraduate engineering programs. Regardless of the type of organization or institution, sustainable diversity and inclusion integration requires difficult conversations that can correspond with locale‐specific interventions and deep cultural transformation. We led a series of design sessions with stakeholders from two undergraduate engineering programs at a large, Midwestern, research university aimed at creating prototype solutions to diversity and inclusion problems. Following the sessions, we conducted interviews with 19 stakeholders to understand their perceptions of the design process in facilitating both difficult conversations and in enacting meaningful change. Our study uncovered that organizational cultures impacted participants' perceptions of change possibilities and their role in change. We conclude with recommendations for adopting design practices and communication‐as‐design processes to create structures and interactive approaches for facilitating conversations toward inclusionary organizational change.